Investigation of atomic and molecular processes in Hα emission through modelling of measured Hα emissivity profile using DEGAS2 in the ADITYA tokamak. (23rd May 2019) - Dey, Ritu; Chowdhuri, M.B.; Ghosh, Joydeep; Manchanda, R.; Yadava, Nandini; Ramaiya, N.; Banerjee, S.; Nagora, U.C.; Atrey, P.K.; Raval, J.V.; Shankar Joisa, Y.; Tanna, R.L.; et al.
Abstract: In order to understand the atomic and molecular processes involved in the emission of the hydrogen Balmer alpha (H ) spectral line from tokamak plasmas, the measured radial profile of H emissivity in ADITYA tokamak discharges has been modeled using the DEGAS2 neutral particle transport code. The radial profile of emissivity has been measured using a 1.0 m multi-track spectrometer and with PMT array based space-resolved visible spectroscopic diagnostics involving interference filters. The radial profile of the neutral hydrogen density has been obtained using the DEGAS2 code by reproducing the experimentally observed H emissivity profile. It has been found that the neutral density falls by 80–200 times at the plasma center compared to its maximum value at the plasma edge near the limiter ( ). Detailed investigation of the contributions of atomic and molecular processes involved in H emission reveals the significant presence of hydrogen molecules and molecular ions within  ̃4 cm of the limiter radius. The contributions from processes involving H ions are found to be higher than those from the molecular hydrogen dissociation with H dissociative recombination dominating over H dissociation at the extreme edge of the plasma.